2023
DOI: 10.1073/pnas.2209177120
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial control of microglial phagocytosis by the translocator protein and hexokinase 2 in Alzheimer’s disease

Abstract: Microglial phagocytosis is an energetically demanding process that plays a critical role in the removal of toxic protein aggregates in Alzheimer’s disease (AD). Recent evidence indicates that a switch in energy production from mitochondrial respiration to glycolysis disrupts this important protective microglial function and may provide therapeutic targets for AD. Here, we demonstrate that the translocator protein (TSPO) and a member of its mitochondrial complex, hexokinase-2 (HK), play critical roles in microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 79 publications
0
20
1
Order By: Relevance
“…Moreover, we found that the bioenergetic rates of TSPO -/- astrocytes did not change significantly between glucose and glucose-free conditions, and TSPO -/- astrocytes secreted significantly less L-lactate in the presence of glucose. This contrasts with a recent publication demonstrating that TSPO deficiency in microglia increases lactate production and glycolysis 55 . The difference between these findings may be due to fundamental differences in the metabolic machinery of astrocytes (which express relatively high amounts of CPT1a 35 ) and microglia (which express less CPT1a than astrocytes 34,35 ) underlying the resulting metabolic profile.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Moreover, we found that the bioenergetic rates of TSPO -/- astrocytes did not change significantly between glucose and glucose-free conditions, and TSPO -/- astrocytes secreted significantly less L-lactate in the presence of glucose. This contrasts with a recent publication demonstrating that TSPO deficiency in microglia increases lactate production and glycolysis 55 . The difference between these findings may be due to fundamental differences in the metabolic machinery of astrocytes (which express relatively high amounts of CPT1a 35 ) and microglia (which express less CPT1a than astrocytes 34,35 ) underlying the resulting metabolic profile.…”
Section: Discussioncontrasting
confidence: 74%
“…Fairley et al . 55 recently observed that TSPO also forms a complex with HK2, the rate-limiting enzyme of glycolysis. Because microglia express low or no levels of CPT1a 34,35 , a TSPO-CPT1a interaction is less likely to be detected/present in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction can be “sensed” by NLRP3 inflammasome 60 to induce proinflammatory responses characterized by IL‐1β production. Mitochondrial dysfunction can further disrupt the mechanism fueling phagocytosis, 14,61 thereby impairing the clearance of toxic Aβ species as we showed here (Figure 6). Significantly, BHB was able to rectify these interwoven abnormalities.…”
Section: Discussionmentioning
confidence: 64%
“…Studies have reported that CS-induced mtROS in COPD patients contributes to an alteration in mitochondrial fission and fusion proteins [ 44 , 45 , 46 ], increased oxidative stress gene signatures [ 47 ], lower mitochondrial membrane potential and ATP levels [ 48 ], impaired mitophagy and concomitant aggregation of damaged and dysfunctional mitochondria [ 35 , 49 , 50 ], and necrosis [ 51 , 52 , 53 ]. In line with this, immune cells in COPD exhibit altered metabolic function, including glycolysis and fatty acid oxidation [ 54 , 55 , 56 , 57 , 58 ], which are important processes required for ATP production to fuel energy demanding immune functions [ 59 ]. Subsequently, immune cells in COPD exhibit impaired immune functions, including phagocytosis, altered viral response, and increased cytokine production [ 60 , 61 , 62 ], suggesting a self-perpetuating cycle in which ROS exposure both initiates and maintains mitochondrial and immune cell dysfunction in COPD, contributing to widespread destruction of the airways.…”
Section: Oxidative Stress In Copdmentioning
confidence: 99%